Silicate rocks as an alternative potassium fertilizer for upland rice and common bean crops - Soratto, Rogério Peres; Crusciol, Carlos Alexandre Costa; Campos, Murilo de; Costa, Claudio Hideo Martins da; Gilabel, Amanda Prado; Castro, Gustavo Spadotti Amaral; Ferrari Neto, Jayme (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the efficiency of molten and ground alkaline potassium-silicate rocks (K1) and of ground phonolite rock (K2) as sources of potassium for upland rice (Oryza sativa) and common bean (Phaseolus vulgaris) crops, in comparison with the traditional source (KCl). Two experiments – one with each crop – were conducted on a Typic Haplorthox in a randomized complete block design with four replicates. The treatments consisted of three sources (KCl, K1, and K2) and four rates (0, 20, 40, and 80 kg ha-1 K2O) of K. Regardless of the used source, K fertilization increased the leaf K content and grain yield of the upland rice and common bean crops. The agronomic efficiency index (AEI) of the alternative K sources varied according to the crop. For upland rice, the AEI of K2 was 8% higher than that of KCl at the recommended K rate, but similar at the highest rate. For common bean, the AEI values of K1 were close to that of KCl at the rates of 40 and 80 kg ha-1 K2O. The alternative sources K1 and K2 supply K and increase the grain yield of common bean and upland rice, respectively, similarly to KCl.